1, 2-Alkylarylation of activated alkenes with dual C–H bonds of arenes and alkyl halides toward polyhalo-substituted oxindoles. Issue 11 (13th November 2014) - Liu, Yu; Zhang, Jia-Ling; Song, Ren-Jie; Li, Jin-Heng
Abstract : Alkylarylation of N -arylacrylamides with alkyl halides through selective scission of the C(sp 3 )–H bond adjacent to halide atoms is presented. Abstract : We describe here a new visible light facilitated radical strategy for 1, 2-alkylarylation of activated alkenes with a C(sp 2 )–H bond of arenes and a C(sp 3 )–H bond of alkyl halides. This method achieves selective scission of the C(sp 3 )–H bond adjacent to halide atoms leading to a halo-substituted alkyl radical, and provides a new synthetic utilization of aryl halides toward polyhalo-substituted oxindoles in good to excellent yields. Moreover, the concise transformation of the products, polyhalo-substituted oxindoles, into vinyl halides and alkynyl halides was also illustrated.